The Monarch in contemporary Malaysia - Nazrin Shah Raja (Institute of Southeast Asian Studies, 2004)
This paper was delivered by His Royal Highness Raja Nazrin Shah at a Public Lecture organized by the Institute of Southeast Asian Studies in Singapore on 27 July 2004.